On the Complexity of Linear Programming (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
In this paper we show a simple treatment of the complexity of Linear Programming. We describe the short step primal-dual path following algorithm and show that it solves the linear programming problem.